1988
DOI: 10.1037/0012-1649.24.5.729
|View full text |Cite
|
Sign up to set email alerts
|

Young adults' perceptions of their relationships with their parents: Individual differences in connectedness, competence, and emotional autonomy.

Abstract: Seventy-eight women and 72 men between 22 and 32 years of age completed an interview assessing five aspects of autonomy (independence, decision making, personal control, self-assertion, and selfother responsibility) and five aspects of relatedness (empathy, closeness, communication, concern, and respect) in their relationships with each of their parents. Factor analyses-resulting in congruent solutions for descriptions of mothers and fathers-reduced these data by identifying three relationship dimensions descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
91
1
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 29 publications
(41 reference statements)
7
91
1
2
Order By: Relevance
“…Emerging adults, at least in Western cultures, are expected to develop higher levels of individuation, displayed in the capacity to rely on oneself and to make independent decisions and follow through with them (Arnett, 2000;Hauser & Greene, 1991;Steinberg, 2002). This developmental task is achieved within a continuous close and supportive relationship with parents, when an emerging adult has the feeling that his or her parents give their blessing and acquiesce in his or her becoming a separate adult and developing a mature relationship with them (Frank, Avery, & Laman, 1988).…”
mentioning
confidence: 99%
“…Emerging adults, at least in Western cultures, are expected to develop higher levels of individuation, displayed in the capacity to rely on oneself and to make independent decisions and follow through with them (Arnett, 2000;Hauser & Greene, 1991;Steinberg, 2002). This developmental task is achieved within a continuous close and supportive relationship with parents, when an emerging adult has the feeling that his or her parents give their blessing and acquiesce in his or her becoming a separate adult and developing a mature relationship with them (Frank, Avery, & Laman, 1988).…”
mentioning
confidence: 99%
“…Theorists have long agreed that same-gender parent-child relationships are qualitatively different from opposite-gender parent-child relationships (e.g., Chodorow, 1974;Frank et al, 1988). In fact, research has shown that mothers and daughters have closer relationships in their adult years than mothers and sons, fathers and daughters, and fathers and sons (Rossi, 1989).…”
Section: Demographic Characteristics and Relationshipsmentioning
confidence: 99%
“…Still, other research has more heavily emphasized the quality of the affectional bond and independence in the relationship (e.g., Cicirelli, 1980Cicirelli, , 1995Frank, Avery, & Laman, 1988;Shmotkin, 1999). For example, Frank and colleagues (1988) proposed three dimensions to describe the relationships between adult children and their parents:…”
Section: Relationship Characteristicsmentioning
confidence: 99%
“…Frank, Avery, and Laman (1988) proposed three dimensions, connectedness (empathy, communication, and emotional closeness), competence (ability to make decisions independent of their parents), and emotional autonomy (respect, personal control, and self-assertion in the relationship), suggesting that emotional closeness as well as relationship control predict relationship quality. Other important dimensions include adult children's attributions for parents' behaviors (Fincham, Beach, Arias, & Brody, 1998) and sense of interpersonal control (Cook, 1993).…”
Section: Adult Child-parent Relationships Relationship Characteristicsmentioning
confidence: 99%